Pengembangan modul interaktif berbasis steam untuk Siswa kelas IV di Sekolah Dasar - Nika Triyana (COLLASE (Creative of Learning Students Elementary Education), 2023)
The purpose of this study was to determine the feasibility of STEAM-based interactive modules in improving students' critical thinking skills. This research is motivated during the learning process in the classroom, students tend to be passive, their curiosity is very low and enthusiasm in the learning process is also very low. This research is a development research using the Borg and Gall model. Data collection techniques with interviews, questionnaires and tests. The data analysis technique in this study used descriptive analysis techniques by analyzing validation data by expert validators and practitioners. The results showed that the results of the assessment of the three validators showed good results, the assessment of the validators was also converted into the feasibility of a module including validator 1 with a score of 90 in the "Very Good/Very Eligible" category, validator 2 with a score of 75 in the "Good/Decent" category and validaor 3 with a score of 84 with the category "Very Good/Very Decent". While the teacher's response showed 87.5% results and student responses showed 88% results. It can be concluded that from the assessment of the validators, the module is feasible to use for class IV elementary school learning.